Pendidikan Kesehatan Mengenai Stunting Di Puskesmas Pacet Tahun 2022 - Rika Susanti (BADAN PENERBIT STIEPARI PRESS, 2022)
The nutritional status of toddlers is the health condition of toddlers which is determined by the degree of physical need for energy and nutrients obtained from food or foods whose physical impacts can be measured using anthropometry. Methods for implementing activities or strategies used to increase the knowledge of mothers of toddlers about balanced nutrition in toddlers, nutritional problems with stunting and maintaining normal nutritional status. After the counseling activities were carried out, participants were given a questionnaire to determine changes in the mother's knowledge and understanding of the material provided by the service team. As for knowledge before and after the nutrition education activities were carried out, it was found that the level of knowledge from 30 respondents was more than half, 20 (66.6%) mothers had low knowledge about balanced nutrition and after the counseling was carried out, 5 (16.7%) mothers had sufficient knowledge, 25 (83%) 3%) mothers have good knowledge. Increasing the knowledge of mothers of toddlers about balanced nutrition in toddlers is expected to improve the attitudes and actions of mothers in providing balanced nutrition to toddlers so that the nutritional status of toddlers is in the normal category.